2008
DOI: 10.1007/s10512-008-9027-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the technological parameters of a high-temperature reactor with solid coolant in the electricity generating regime

Abstract: Questions of choosing a thermodynamic cycle and the working parameters for a high-temperature reactor with solid coolant are examined. The results of investigations showing that such a reactor can be used in a power-generating unit of a nuclear power plant with high unit capacity with well-understood turbine facilities operating on superheated steam are presented.The thermodynamic cycles and working parameters of a reactor facility for electricity generation based on an innovative design of a high-temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The effect of turning of the particles can be even greater, but no simple methods of evaluating it have been found. On the basis of calculations and the arrangement of the experimental facility, it can be concluded that the experimentally determined heat-emission coefficients for particles with diameter about 1 mm do not contain any errors due to thermal inertia, and the effect of thermal inertia is negligibly small in computational assessments of a power reactor [3]. However, thermal inertia and internal stresses in heat-carrying elements grow very rapidly as the size of the elements increases.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…The effect of turning of the particles can be even greater, but no simple methods of evaluating it have been found. On the basis of calculations and the arrangement of the experimental facility, it can be concluded that the experimentally determined heat-emission coefficients for particles with diameter about 1 mm do not contain any errors due to thermal inertia, and the effect of thermal inertia is negligibly small in computational assessments of a power reactor [3]. However, thermal inertia and internal stresses in heat-carrying elements grow very rapidly as the size of the elements increases.…”
mentioning
confidence: 98%
“…The basic ideas of the reactor design and assessment of the actually attainable technological parameters are presented in [2][3][4], and the experimental results of a study of the thermophysical characteristics of the flow of heat-carrying particles are presented in [5]. The particulars of the proposed nuclear reactor are as follows:…”
mentioning
confidence: 99%
See 3 more Smart Citations